Eliminating the Attentional Blink through Binaural Beats: A Case for Tailored Cognitive Enhancement - Reedijk, Susan A.; Bolders, Anne; Colzato, Lorenza S.; Hommel, Bernhard (Frontiers in Psychiatry, 2015)
Enhancing human cognitive performance is a topic that continues to spark scientific interest. Studies into cognitive enhancement techniques often fail to take inter-individual differences into account, however, which leads to underestimation of the effectiveness of these techniques. The current study investigated the effect of binaural beats, a cognitive enhancement technique, on attentional control in an attentional blink task. As predicted from a neurocognitive approach to cognitive control, high-frequency binaural beats eliminated the attentional blink, but only in individuals with low spontaneous eye-blink rates (indicating low striatal dopamine levels). This suggests that the way in which cognitive enhancement techniques, such as binaural beats, affect cognitive performance depends on inter-individual differences.